Perancangan dan Implementasi Layanan Sistem Informasi Berbasis Cloud Computing Software as a Service pada UMKM di Jawa Tengah - Mohammad Hidayatul Holili; Susilo Adi; Didik Sofian Haryadi (Universitas Kristen Indonesia Toraja, 2022)
Designing and Implementing Cloud Computing Based Information System Services Software As A Service for MSMEs in Central Java. Able to create and apply Cloud Computing Based Information Services Software As A Service to MSMEs in Central Java. Design and Implementation of Information System Services Based on Cloud Computing Software as a Service for MSMEs in Central Java. The use of cloud computing software as a service for MSMEs can work according to its objectives because users do not need to make significant investments and only pay according to their needs.